Rogue waves in diatomic acoustic metamaterials with damping effect - Joseph, Mora; Amadou, Yaouba; Douvagai; Justin, Mibaile; İnç, Mustafa; David, Vroumsia; Betchewe, Gambo (Taylor & Francis Ltd, 2026)
The paper addresses the damping effects on MI and on Rogue waves in diatomic acoustic metamaterials. Through the semi-discrete approximation method, we show that the network can be governed by a new form of the generalized coupled nonlinear Schr & ouml;dinger equation (CNLSE). In the linear stability analysis, we generate the MI growth rate, and we assess the damping effect on the MI spectrum. The combination of similarity and Darboux transformations help us to obtain rogue wave solutions (RWs). The acquired RWs are plotted and we observe remarquable influence of the damping effect on their intensities.
Keywords: Diatomic acoustic metamaterials; modulation instability (MI); rogue waves; damping effect